2017
DOI: 10.1007/978-3-319-55982-7_15
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Long-Term Studies to Conservation Practice: The Case of the Bearded Vulture in the Pyrenees

Abstract: Detailed, long-term scientific studies are necessary for conservation purposes, but with the main handicap to have the continual economic support required for them. Behavioural and conservation biology studies need long-term projects to achieve robust data, but managers, administrations and policy-makers need, in most cases, immediate results. Here I show several examples of the research obtained from a long-term study in one of the most threatened species in Pyrenean mountains, the bearded vulture (Gypaetus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 158 publications
(205 reference statements)
0
10
0
Order By: Relevance
“…It is well known that density dependence affects several relevant parameters in population dynamics (Ferrer & Donazar, 1996), including mortality which increases when density increases (e.g., through increasing rates of territorial disputes and fighting among breeders or increasing juvenile starvation), productivity which increases when density decreases, and age of first breeding which decreases when density decreases (Ferrer & Bisson, 2003;Morandini, Benito, Newton, & Ferrer, 2017;Newton, 1998). Variation in productivity is usually included in simulation models but variation in the age of first breeding is largely ignored in PVAs (Antor et al, 2007;Bretagnolle, Inchausti, Seguin, & Thibault, 2004;Evans et al, 2009;Margalida, 2017;Margalida, Colomer, Oro, Arlettaz, & Donázar, 2015;Naveda-Rodríguez, Vargas, Kohn, & Zapata-Ríos, 2016;Radovic & Mikuska, 2009). Nevertheless, in most reintroduction programs a lower than expected age of first breeding was reported (Evans et al, 1999(Evans et al, , 2009Muriel, Ferrer, Casado, Madero, & Calabiug, 2011;Muriel, Ferrer, Casado, & Pérez Calabuig, 2010;Sarrazin, Bagnolinp, Pinna, & Danchin, 1996;Woods et al, 2007) showing that age of first breeding decreases as predicted in a low-density situation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that density dependence affects several relevant parameters in population dynamics (Ferrer & Donazar, 1996), including mortality which increases when density increases (e.g., through increasing rates of territorial disputes and fighting among breeders or increasing juvenile starvation), productivity which increases when density decreases, and age of first breeding which decreases when density decreases (Ferrer & Bisson, 2003;Morandini, Benito, Newton, & Ferrer, 2017;Newton, 1998). Variation in productivity is usually included in simulation models but variation in the age of first breeding is largely ignored in PVAs (Antor et al, 2007;Bretagnolle, Inchausti, Seguin, & Thibault, 2004;Evans et al, 2009;Margalida, 2017;Margalida, Colomer, Oro, Arlettaz, & Donázar, 2015;Naveda-Rodríguez, Vargas, Kohn, & Zapata-Ríos, 2016;Radovic & Mikuska, 2009). Nevertheless, in most reintroduction programs a lower than expected age of first breeding was reported (Evans et al, 1999(Evans et al, , 2009Muriel, Ferrer, Casado, Madero, & Calabiug, 2011;Muriel, Ferrer, Casado, & Pérez Calabuig, 2010;Sarrazin, Bagnolinp, Pinna, & Danchin, 1996;Woods et al, 2007) showing that age of first breeding decreases as predicted in a low-density situation.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, we are greatly overestimating the extinction risk. Unfortunately, this seems to be the prevalent practice in most of the published papers on this topic taking age of first breeding is a fixed value typical of populations at medium to high density (Antor et al, 2007;Bretagnolle et al, 2004;Evans et al, 2009;Margalida, 2017;Margalida et al, 2015;Naveda-Rodríguez et al, 2016;Radovic & Mikuska, 2009).…”
Section: Reintroduced Population Stable Populationsmentioning
confidence: 99%
“…They attain a high symbolic value both for the scientific community and the population in general. Correct management of these species requires accurate knowledge of their behaviour that needs to be based on long-term research plans (Margalida 2017). Nature reserves are the appropriate scenario for sustaining this type of studies.…”
Section: Conservation Versus Stewardship (Franciscans Vs Benedictines)mentioning
confidence: 99%
“…Over the last few decades, it has been shown that longer‐term studies of wildlife populations are of increasing scientific and conservation management importance (Kappeler et al, 2012; Margalida, 2017; Pelton & Van Manen, 1996). This is particularly true of taxa with long life spans such as many species of primates, which require several years of research to adequately document their life histories (Chapman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%